The local scouring phenomenon at bridge abutments terminating in the floodplain zone. - Kouchakzadeh, Salah. (University of Ottawa (Canada), 1996)
This study examines the local scouring phenomenon associated with bridge abutments exposed to combined main-channel (MC) and floodplain (FP) flows. The principal goal of the study was to develop and validate, based on a comprehensive physical-model testing programme that considered different abutment shapes, an improved relationship for predicting maximum scour depth. A relationship was established among sediment size, flow depth and longitudinal channel slope for initiating the threshold condition of bed material movement. This relationship facilitated the selection of sediment size and channel bed slope for the various experiments, which were performed in a compound channel under interacting (combined MC and FP flows) and non-interacting (isolated FP flow) conditions. Clear-water approach-flow conditions were utilized throughout the testing programme. A flow visualization technique was employed to study the various patterns of the combining flows in the MC/FP junction regions. It determined both the flow deflection angle and the extent of the influence zone (a portion of the channel width beyond the abutment) whose discharge, $Q\sb{w}$, contributes to the scour development. Maximum scour depths produced under interacting conditions were observed to be 15% to 30% greater than those observed for non-interacting conditions. This important observation clearly demonstrated the need to properly account for compound-channel effects in the simulation exercise. The scour prediction relationship presented herein is based on a dimensional analysis of the relevant parameters and incorporates the data obtained from the laboratory studies performed in a compound channel using vertical-wall, wing-wall, semi-circular, and spill-through abutment shapes. The model indicates a very good agreement between predicted and observed maximum scour depths for bridge abutments terminating in the FP zone.
Keywords: Engineering, Civil.